Preparation method and application of ceramic isolating membrane on surface of carbon-carbon thermal field structural member
By preparing ceramic isolation film on the surface of carbon-carbon thermal field structural parts, the peeling and blocking problems caused by differences in thermal expansion coefficients are solved, and the continuity and corrosion resistance of ceramic isolation film are achieved, extending service life and reducing preparation costs.
Patent Information
- Application Number
- CN202411994225.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Thermal stress and mechanical stress caused by the difference in thermal expansion coefficient during the crystal drawing process of carbon-carbon thermal field structural parts cause peeling and blocking to fall off the inner surface of the pot, which seriously reduces the service life and increases the cost of crystal drawing.
A method of preparing a ceramic isolation film on the surface of carbon-carbon thermal field structural parts is adopted, and a continuous ceramic isolation film is formed by impregnating the carbon cloth with ceramic impregnation liquid, using ceramic adhesive and ceramic slurry, and a continuous ceramic isolation film is formed by isostatic penetration and ceramic sintering.
The continuous and high temperature and corrosion resistance of ceramic isolation film are achieved, the service life of carbon-carbon thermal field structural parts is extended, and the preparation cost is reduced.
Smart Images

Figure BDA0005224253070000071
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of carbon-carbon composite materials, and in particular to a method for preparing and applying a ceramic isolation film on the surface of a carbon-carbon thermal field structure. Background Art
[0002] Carbon-carbon thermal field structural parts generally include carbon-carbon guide tubes, carbon-carbon crucible sides and insulation tubes. For example, the carbon-carbon crucible side has the advantages of low density, high specific strength, high thermal conductivity, low expansion coefficient, good thermal shock resistance, and high dimensional stability, and has become the core thermal field structural part of the single crystal silicon vertical pulling furnace. During the crystal pulling process, the carbon-carbon crucible side is adjacent to the quartz crucible that holds the silicon material. The quartz crucible and the carbon-carbon crucible side are decarbonized and silicified at high temperatures, and loose, discontinuous, and brittle silicon carbide is generated on the inner surface of the crucible side. The difference in thermal expansion coefficients between the crucible side and silicon carbide causes thermal stress on the inner surface of the crucible side during repeated crystal pulling processes, and external mechanical stress is generated during the process of taking the crystal rod. The inner surface of the crucible side peels off or even falls off on a large scale, which seriously reduces the service life of the crucible side and increases the cost of crystal pulling.
[0003] At present, because the thermal expansion coefficient of silicon carbide is similar to that of the carbon-carbon crucible side, it is often used to improve the corrosion resistance of the crucible side. Patent CN103553711A proposes to prepare a composite coating of silicon carbide coating / silicon coating / silicon nitride coating on the surface of the carbon / carbon composite insulation tube to effectively inhibit the corrosion of the silicon vapor generated after the silicon material is melted on the surface of the carbon / carbon insulation tube, but the cost of preparing silicon carbide by chemical vapor infiltration is high, the cycle is long, and the efficiency is low. CN11848201A proposes to use a plasma spraying process to form a SiC / Si coating on the surface of the carbon-carbon crucible side to improve the anti-siliconization corrosion ability of the carbon-carbon crucible side, thereby increasing the service life of the crucible side, but due to the appearance characteristics of the crucible side, it is difficult to achieve a uniform coating on the crucible side surface by using a plasma spraying process, and the obtained coating is thin and the thermal expansion coefficient does not match, and the ability to inhibit silicon vapor corrosion is very limited. In addition, the raw material cost of the impregnation cracking SiC method is high, the cycle is long, and the surface coating is discontinuous; the siliconization method is high in cost, has a large amount of silicon residue, and is also prone to the risk of cracking caused by the mismatch of the thermal expansion coefficients of silicon and carbon. At the same time, the mechanical external force generated by knocking during the actual process of taking the crystal rod will increase the risk of the silicon carbide layer falling off, so it is very necessary to develop a simple, short-cycle, and low-cost method to improve the corrosion resistance of the crucible. Summary of the invention
[0004] In order to make the ceramic isolation film on the surface of the carbon-carbon thermal field structure continuous and corrosion-resistant and extend the service life of the carbon-carbon thermal field structure, the present application provides a preparation method and application of the ceramic isolation film on the surface of the carbon-carbon thermal field structure.
[0005] In a first aspect, the present application provides a method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure, using the following technical solution: A method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure, comprising the following preparation steps: S1, preparing a ceramic impregnation solution, and impregnating a carbon cloth with the ceramic impregnation solution to obtain an impregnated carbon cloth; S2, preparing ceramic adhesive; S3, preparing ceramic slurry; S4, grinding the inner surface of the carbon-carbon thermal field structure, coating the ceramic adhesive, pasting the impregnated carbon cloth and brushing the ceramic slurry, and then performing isostatic pressure penetration; S5. Ceramic-sintering the carbon-carbon thermal field structure after isostatic pressing infiltration to form a ceramic isolation film on the inner surface of the carbon-carbon thermal field structure.
[0006] By adopting the above technical scheme, by impregnating the carbon cloth in the ceramic impregnation liquid, the carbon cloth can enhance the toughness and strength of the ceramic impregnation liquid through its own high strength and excellent tensile strength, thereby improving the continuity of the ceramic isolation membrane; by using the ceramic adhesive, the carbon cloth reinforced ceramic isolation membrane and the carbon-carbon thermal field structure can be tightly bonded, so as to further alleviate the mismatch force caused by the inconsistency of the thermal expansion coefficient between the ceramic isolation membrane and the carbon-carbon crucible side. After high-temperature treatment, the ceramic isolation membrane is well bonded to the inner surface of the crucible side without cracks or powder chips; the inner surface of the carbon-carbon thermal field structure is polished so that its inner surface has a completely frosted texture, which can fully contact with the ceramic adhesive and has good bonding properties with the ceramic adhesive. Better yet, after bonding with the impregnated carbon cloth, apply ceramic slurry, and after isostatic pressing and infiltration, make the impregnated carbon cloth close to the inner surface of the carbon-carbon thermal field structure, and then perform vitrification sintering under vacuum conditions to form a continuous and dense ceramic isolation membrane on the inner surface of the carbon-carbon thermal field structure. Compared with the prior art, the method of preparing a ceramic isolation membrane on the inner surface of a carbon-carbon thermal field structure in the present application is not only simple to operate, but also shortens the preparation cycle and reduces the preparation cost. The prepared ceramic isolation membrane is continuous, resistant to high temperatures and has excellent corrosion resistance. When applied to, for example, a carbon-carbon crucible side, it can better prevent the quartz crucible from directly contacting the carbon-carbon crucible side, eliminate silicification and decarbonization, and does not change the use characteristics of the carbon-carbon crucible side in crystal pulling, thereby making up for the shortcomings of the prior art.
[0007] Preferably, the ceramic impregnation solution comprises the following raw materials in percentage by mass: 1-5% silicon carbide, 5-10% silicon powder, and the remainder is aluminum sol.
[0008] By adopting the above technical solution, the ceramic impregnation liquid prepared in the present application has a simple formula, does not require other auxiliary materials, has good adhesion to the carbon cloth, and has good film-forming properties after high-temperature firing.
[0009] Preferably, the carbon cloth is any one of 1K-12K.
[0010] By adopting the above technical solution, 1K-12K carbon cloth has the advantages of high strength and good tensile properties, can withstand large external forces without being easily deformed, and has excellent corrosion resistance. The present application uses 1K-12K carbon cloth to form a continuous ceramic isolation film on the inner surface of the carbon-carbon thermal field structure.
[0011] Preferably, the ceramic adhesive comprises the following raw materials in percentage by mass: 0.15-0.4% curing agent, 5-15% carbon felt powder, 15-25% asphalt powder, 3-10% graphite powder, 1-5% silicon carbide, 5-10% silicon powder, and the remainder is furan resin.
[0012] By adopting the above technical solution and selecting the raw material and dosage of the ceramic adhesive, the carbon-carbon thermal field structure can be tightly bonded to the impregnated carbon cloth.
[0013] Preferably, the ceramic slurry comprises the following raw materials in percentage by mass: 50-70% silicon powder, 5-20% ethanol, and the remainder is phenolic resin.
[0014] By adopting the above technical solution, ethanol and phenolic resin can disperse the silicon powder evenly.
[0015] Preferably, in S4, the grinding depth of the inner surface of the carbon-carbon thermal field structure is 0.5-1.1 mm.
[0016] By adopting the above technical solution, the grinding thickness of the inner surface of the carbon-carbon thermal field structure also has a certain influence on the ceramic isolation membrane. A low grinding depth is not conducive to the bonding of the inner surface of the carbon-carbon thermal field structure and the ceramic adhesive, so that the ceramic isolation membrane and the inner surface of the carbon-carbon thermal field structure form pores, which makes the ceramic isolation membrane less continuous and prone to cracks.
[0017] Preferably, the coating thickness of the ceramic adhesive is 0.2-0.8 mm.
[0018] By adopting the above technical solution, the thickness of the ceramic adhesive can make the impregnated carbon cloth have good adhesion when it is 0.2-0.8 mm.
[0019] As a preference, the parameter conditions of the isostatic penetration are as follows: Evacuate the chamber and raise the temperature to 170-200°C for 5-8 hours. After the heating is completed, keep the temperature for 1-2 hours. When the temperature reaches 50-70°C, pressurize the chamber to 1.5-2.5MPa. Maintain the pressure during the heating and insulation process.
[0020] As a preference, the parameters of the porcelain sintering are as follows: Evacuate the chamber and heat to 1550-1650℃ for 40-50h. After heating, keep warm for 2-4h.
[0021] As a preferred embodiment, if the temperature rises too fast, it is not conducive to the close contact between the impregnated carbon cloth and the inner surface of the carbon-carbon thermal field structure, thereby affecting the continuity of the ceramic isolation membrane.
[0022] In a second aspect, the present application provides an application of a method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure, using the following technical solution: The invention discloses an application of a method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure. The method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure is applied to a carbon-carbon guide tube, a carbon-carbon crucible side or a heat preservation tube.
[0023] By adopting the above technical scheme, the method for preparing the ceramic isolation film on the surface of the carbon-carbon thermal field structure of the present application can be applied to various carbon-carbon thermal field structures such as carbon-carbon guide tubes, carbon-carbon crucible sides and insulation tubes, and has strong adaptability.
[0024] In summary, the present application includes at least one of the following beneficial technical effects: 1. By impregnating the carbon cloth in the ceramic impregnation liquid, the carbon cloth can enhance the toughness and strength of the ceramic impregnation liquid through its own high strength and excellent tensile strength, thereby improving the continuity of the ceramic isolation membrane; the use of ceramic adhesive can achieve close bonding between the carbon cloth reinforced ceramic isolation membrane and the carbon-carbon thermal field structure, thereby further alleviating the mismatch force caused by the inconsistency of the thermal expansion coefficient between the ceramic isolation membrane and the carbon-carbon thermal field structure. After high-temperature treatment, the ceramic isolation membrane is well bonded to the inner surface of the crucible side, and no cracks or powder are generated.
[0025] 2. Compared with the prior art, the method of preparing a ceramic isolation membrane on the inner surface of a carbon-carbon thermal field structure in the present application is not only easy to operate, but also shortens the preparation cycle and reduces the preparation cost. The prepared ceramic isolation membrane is continuous, resistant to high temperatures and has excellent corrosion resistance. When applied to the carbon-carbon crucible side, it can better prevent the quartz crucible from directly contacting the carbon-carbon crucible side, eliminate siliconization and decarbonization, and does not change the use characteristics of the carbon-carbon crucible side in crystal pulling, greatly extending the service life of the carbon-carbon thermal field structure.
[0026] 3. After the carbon-carbon crucible side prepared by the method of preparing a ceramic isolation membrane on the inner surface of a carbon-carbon thermal field structure of the present application was subjected to a 1600°C, 60-hour silicification erosion test, the ceramic isolation membrane on its inner surface showed no corrosion, the ceramic isolation membrane was well bonded to the substrate, no cracks appeared, no powder fell off, and the weight loss rate was between 0.010-0.016%. This indicates that the method of preparing a ceramic isolation membrane on the surface of a carbon-carbon crucible side of the present application can form a continuous, corrosion-resistant ceramic isolation membrane on the inner surface of the carbon-carbon crucible side, which can greatly extend the service life of the carbon-carbon crucible side. DETAILED DESCRIPTION
[0027] The present application is further described in detail below in conjunction with the specific contents.
[0028] raw material The raw materials used in this application are all purchased from the market, among which the particle size of silicon carbide powder is 500 mesh, and the silicon content is ≥99%; the particle size of silicon powder is 600 mesh, and the silicon dioxide content is ≥97%; the aluminum sol is industrial grade aluminum sol; the model of furan resin is 102, and the content is ≥98%; the model of curing agent is MDI-50; the particle size of carbon felt powder is 100 mesh; the particle size of asphalt powder is 100 mesh; and the particle size of graphite powder is 2000 mesh. Example
[0029] Example 1 A method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure, taking a carbon-carbon crucible as an example, comprises the following preparation steps: S1, preparing a ceramic impregnation liquid: adding silicon carbide powder and silicon powder to aluminum sol at one time, wherein the mass percentages of silicon carbide powder and silicon powder are 3% and 7% respectively, and the remainder is aluminum sol, stirring evenly, and standing for 24 hours for use; S2. Stir the ceramic impregnation liquid evenly, put in 3K carbon cloth, soak for 10 minutes, and roll the impregnated carbon cloth on a small impregnation machine to obtain an impregnated 3K carbon cloth with a thickness of 0.25 mm, and let it dry naturally for 2 hours for use; S3. Prepare ceramic adhesive: add 60% furan resin, 0.2% curing agent, 7% carbon felt powder, 20% asphalt powder, 5% graphite powder, 1.8% silicon carbide and 6% silicon powder into a stainless steel container in order according to the percentage by mass. Stir for 5 minutes each time adding one material. After all the materials are added, continue stirring for 40 minutes until the materials are uniform. Seal and let stand at 22-30°C for 24 hours for use. S4, prepare ceramic slurry: according to the mass percentage: mix 40% phenolic resin, 52% silicon powder, and 8% ethanol, stir evenly, and let stand for 24 hours for use; S5, grinding the inner surface of the carbon-carbon crucible to a grinding depth of 1 mm, cleaning, and drying; S6. Coat the inner surface of the carbon-carbon crucible with a ceramic adhesive having a thickness of 0.7 mm, and evenly and evenly adhere the impregnated 3K carbon cloth to the inner surface of the polished carbon-carbon crucible through the ceramic adhesive. Then, evenly apply a layer of ceramic slurry on the surface of the impregnated 3K carbon cloth. The coating thickness is 0.15 mm. Then, perform isostatic penetration. After evacuation, evenly heat to 180°C for 6 hours, and keep at 180°C for 2 hours. When the temperature is raised to 60°C, the pressure is increased to 1.8 MPa, and the pressure is maintained at 1.8 MPa during the heating and insulation process. After the heat preservation in S7 and S6 is completed, ceramic sintering is carried out, vacuum is drawn, and then the temperature is evenly increased to 1600°C for 40 hours. The temperature is kept at 1600°C for 2 hours and naturally cooled. The continuous ceramic isolation film on the inner surface of the carbon-carbon crucible side is prepared.
[0030] Example 2 A method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure, taking a carbon-carbon crucible as an example, comprises the following preparation steps: S1. Prepare ceramic impregnation solution: add silicon carbide powder and silicon powder into aluminum sol at once, the mass percentage of silicon carbide powder and silicon powder is 5% and 8% respectively, and the balance is aluminum sol, stir evenly, and let stand for 24 hours for use; S2. Stir the ceramic impregnation liquid evenly, put in 1K carbon cloth, soak for 10 minutes, and roll the impregnated carbon cloth on a small impregnation machine to obtain an impregnated 1K carbon cloth with a thickness of 0.2 mm, and let it dry naturally for 1.5 hours for use; S3. Prepare ceramic adhesive: add 52% furan resin, 0.2% curing agent, 10% carbon felt powder, 20% asphalt powder, 10% graphite powder, 2% silicon carbide and 5.8% silicon powder into a stainless steel container in order according to the percentage by mass. Stir for 5 minutes each time adding one material. After all the materials are added, continue stirring for 40 minutes until the materials are uniform. Seal and let stand at 22-30°C for 24 hours for use. S4, prepare ceramic slurry: according to the mass percentage: mix 45% phenolic resin, 50% silicon powder, and 5% ethanol, stir evenly, and let stand for 24 hours for use; S5, grinding the inner surface of the carbon-carbon crucible to a grinding depth of 1 mm, cleaning, and drying; S6. Coat the inner surface of the carbon-carbon crucible with a ceramic adhesive having a thickness of 0.55 mm, and evenly and evenly adhere the impregnated 1K carbon cloth to the inner surface of the polished carbon-carbon crucible through the ceramic adhesive. Then, evenly apply a layer of ceramic slurry on the surface of the impregnated 1K carbon cloth. The coating thickness is 0.25 mm. Then, perform isostatic penetration. After evacuation, evenly heat to 180°C for 5 hours, and keep at 180°C for 2 hours. When the temperature is raised to 60°C, the pressure is increased to 1.8 MPa, and the pressure is maintained at 1.8 MPa during the heating and insulation process. After the heat preservation in S7 and S6 is completed, ceramic sintering is carried out, vacuum is drawn, and then the temperature is evenly increased to 1600°C for 40 hours. The temperature is kept at 1600°C for 2 hours and naturally cooled. The continuous ceramic isolation film on the inner surface of the carbon-carbon crucible side is prepared.
[0031] Example 3 A method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure component is different from that in Example 2 in that, in S2, the carbon cloth is 12K carbon cloth, and the remaining steps are the same as those in Example 2.
[0032] Example 4 A method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure component is different from that in Example 2 in that, in S5, the inner surface of the carbon-carbon crucible side is polished to a thickness of 0.5 mm, and the remaining steps are the same as those in Example 2.
[0033] Example 5 A method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure component is different from that in Example 2 in that, in S6, the thickness of the ceramic adhesive coated on the inner surface of the carbon-carbon crucible side is 0.2 mm, and the remaining steps are the same as those in Example 2.
[0034] Example 6 A method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure component is different from that in Example 2 in that, in S6, the thickness of the ceramic adhesive coated on the inner surface of the carbon-carbon crucible side is 0.8 mm, and the remaining steps are the same as those in Example 2.
[0035] Comparative Example Comparative Example 1 A method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure component is different from that in Example 2 in that in S5, the inner surface of the carbon-carbon crucible is polished to a depth of 0.2 mm, and the remaining steps are the same as those in Example 2.
[0036] Comparative Example 2 A method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure is different from that in Example 2 in that in S6, no pressurization is performed when the temperature is raised to 60° C., and the remaining steps are the same as those in Example 2.
[0037] Comparative Example 3 A method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure component is different from that in Example 2 in that after the insulation in S7 is completed, ceramic sintering is performed, vacuum is evacuated, and then the temperature is uniformly raised to 1600°C for 25 hours, and the temperature is kept at 1600°C for 2 hours, and then naturally cooled. The remaining steps are the same as in Example 2.
[0038] Comparative Example 4 A method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure component is different from that in Example 2 in that the impregnated 1K carbon cloth is replaced with a ceramic impregnation liquid of equal thickness in S6, and the remaining steps are the same as those in Example 2.
[0039] Performance testing Detection method / test method According to the preparation methods of Examples 1-6 and Comparative Examples 1-4, carbon-carbon crucible sides with ceramic isolation films on the inner surfaces were prepared respectively, and then subjected to a silicidation erosion test at 1600°C for 60 hours. It was then observed whether the ceramic isolation film had any corrosion, whether the ceramic isolation film was well bonded to the substrate, whether there were any cracks, whether there was any powder falling, and the weight loss rate was calculated. The results are shown in Table 1.
[0040] Table 1 Test results of Examples 1-6 and Comparative Examples 1-4 It can be seen from Examples 1-6 and Comparative Examples 1-3, as well as the test data in Table 1, that after the carbon-carbon crucible side prepared in the present application was subjected to a 1600°C, 60-hour silicification erosion test, the ceramic isolation membrane on the inner surface showed no corrosion, the ceramic isolation membrane was well bonded to the substrate, no cracks occurred, no powder fell off, and the weight loss rate was between 0.010-0.016%. This indicates that the preparation method of the ceramic isolation membrane on the surface of the carbon-carbon crucible side of the present application can form a continuous, corrosion-resistant ceramic isolation membrane on the inner surface of the carbon-carbon crucible side, which can greatly extend the service life of the carbon-carbon crucible side.
[0041] It can be seen from the test data of Examples 1-2 and Comparative Example 4 that by preparing a ceramic impregnation liquid and using it to prepare an impregnated carbon cloth, and also preparing a ceramic adhesive and a ceramic slurry, the inner surface of the carbon-carbon crucible ridge is polished so that the inner surface is completely frosted, which can be fully in contact with the ceramic adhesive and has better adhesion with the ceramic adhesive. Then, after bonding with the impregnated carbon cloth, the ceramic slurry is applied, and after isostatic pressure penetration, the impregnated carbon cloth is closely attached to the inner surface of the carbon-carbon crucible ridge, and then porcelain sintering is performed under vacuum conditions to form a continuous ceramic isolation membrane on the inner surface of the carbon-carbon crucible ridge. Under vacuum and high temperature conditions, after the furan resin and other substances in the ceramic adhesive decompose and volatilize, the impregnated carbon cloth and the like can be more closely attached to the inner surface of the carbon-carbon crucible ridge. The carbon cloth can enhance the toughness and strength of the ceramic impregnation liquid through its own high strength and excellent tensile strength, thereby improving the continuity of the ceramic isolation membrane.
[0042] It can be seen from the test data of Examples 1-3 that 1K-12K carbon cloth has the advantages of high strength and good tensile properties, can withstand large external forces without being easily deformed, and has excellent corrosion resistance. The 1K-12K carbon cloth used in this application forms a continuous ceramic isolation film on the inner surface of the carbon-carbon crucible ridge. Combined with Example 4 and Comparative Example 1, the grinding thickness of the inner surface of the carbon-carbon crucible ridge also has a certain effect on the ceramic isolation film. The low grinding depth is not conducive to the bonding between the inner surface of the carbon-carbon crucible ridge and the ceramic adhesive, causing pores to form between the ceramic isolation film and the inner surface of the carbon-carbon crucible ridge, thereby causing the ceramic isolation film to have poor continuity.
[0043] It can be seen from the test data of Example 2 and Examples 5-6 that the thickness of the ceramic adhesive can make the impregnated carbon cloth have good adhesion when it is 0.2-0.8 mm.
[0044] It can be seen from the test data of Example 2 and Comparative Examples 2-3 that the lack of pressurization in S6 or the excessively fast temperature increase in S7 is not conducive to the close contact between the impregnated carbon cloth and the inner surface of the carbon-carbon crucible, thereby affecting the continuity of the ceramic isolation membrane.
[0045] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. A method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure, characterized in that: It comprises the following preparation steps: S1, preparing a ceramic impregnation solution, and impregnating a carbon cloth with the ceramic impregnation solution to obtain an impregnated carbon cloth; S2, preparing ceramic adhesive; S3, preparing ceramic slurry; S4, grinding the inner surface of the carbon-carbon thermal field structure, coating the ceramic adhesive, pasting the impregnated carbon cloth and brushing the ceramic slurry, and then performing isostatic pressure penetration; S5. Ceramic-sintering the carbon-carbon thermal field structure after isostatic pressing infiltration to form a ceramic isolation film on the inner surface of the carbon-carbon thermal field structure.
2. The method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure according to claim 1, characterized in that: The ceramic impregnation solution comprises the following raw materials in percentage by weight: 1-5% silicon carbide, 5-10% silicon powder, and the balance is aluminum sol.
3. The method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure according to claim 1, characterized in that: The carbon cloth is any one of 1K-12K.
4. The method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure according to claim 1, characterized in that: The ceramic adhesive comprises the following raw materials in percentage by weight: 0.15-0.4% curing agent, 5-15% carbon felt powder, 15-25% asphalt powder, 3-10% graphite powder, 1-5% silicon carbide, 5-10% silicon powder, and the remainder is furan resin.
5. The method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure according to claim 1, characterized in that: The ceramic slurry comprises the following raw materials in percentage by weight: 50-70% silicon powder, 5-20% ethanol, and the remainder is phenolic resin.
6. The method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure according to claim 1, characterized in that: In the above S4, the grinding depth of the inner surface of the carbon-carbon thermal field structure is 0.5-1.1 mm.
7. The method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure according to claim 1, characterized in that: The coating thickness of the ceramic adhesive is 0.2-0.8 mm.
8. The method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure according to claim 1, characterized in that: The parameter conditions of the isostatic penetration are as follows: Evacuate the chamber and raise the temperature to 170-200°C for 5-8 hours. After the heating is completed, keep the temperature for 1-2 hours. When the temperature reaches 50-70°C, pressurize the chamber to 1.5-2.5MPa. Maintain the pressure during the heating and insulation process.
9. The method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure according to claim 1, characterized in that: The parameters of the porcelain sintering are as follows: Evacuate the chamber and heat to 1550-1650℃ for 40-50h. After heating, keep warm for 2-4h.
10. Application of a method for preparing a ceramic isolation film on the surface of a carbon-carbon thermal field structure, characterized in that: The method for preparing the ceramic isolation film on the surface of the carbon-carbon thermal field structure is applied to a carbon-carbon guide tube, a carbon-carbon crucible rib and a heat preservation tube.
Citation Information
Patent Citations
Composite coating carbon / carbon composite material crucible and preparation method thereof
CN103553711A
Processing and manufacturing method of carbon / carbon insulation structure
CN102050634A
Low-density carbon / carbon heat preservation material oxidation-resistant coating and preparation process thereof
CN106365692A
Block carbon reinforcement / carbon composite material and preparation method thereof
CN108530099A
Device and method for forming a metal matrix composite vehicle component
CN108698122A